Ideal Cardiovascular Health Index and Its Determinants in a Rural South African Population. Issue 1 (25th November 2020) - Ketelaar, E. J.; Vos, A. G.; Godijk, N. G.; Scheuermaier, K.; Devillé, W.; Tempelman, H.; Coutinho, R. A.; Venter, W. D. F.; Grobbee, D. E.; Klipstein-Grobusch, K.
Background: The ideal cardiovascular health index (CVHI) is a measure to summarize cardiovascular (CV) health, and includes smoking, body-mass index, physical activity, blood pressure, glucose, total cholesterol, and diet. Objective: This study aimed to assess CV health using the CVHI and determinants on CV health in a rural African population, and correlate carotid intima-media thickness (CIMT), a surrogate marker for atherosclerosis, with CVHI. Methods: A cross-sectional analysis was performed on baseline data of the Ndlovu Cohort Study, located in rural South Africa. CVHI score (CVHIs) was calculated by the sum of favourable CVHI factors (range 0 to 7). Logistic regression was performed to examine the association of age, sex, HIV-status, education level, employment status, and income with good CV health (5–7 favourable health factors). Mean CIMT was displayed by poor, intermediate and good CV health. Results: The study included 1927 participants with a mean age of 38.7 years (SD ± 12.8). Of the factors contributing to the CVHI, glucose and total cholesterol scored best; diet least good. Average CVHIs for the population was 4.4 (SD ± 1.2) and 53% of the population had a good CV health. Determinants associated with good CV health were younger age, higher educational attainment, and HIV positivity. CVHIs showed good agreement with CIMT. Conclusion: CVHIs showed that more than half of the participants had a good CV health. Agreement between CVHIs and CIMT indicates potential use of CVHIs as a surrogate marker for CV risk. The study highlights the importance of education for health promotion; good CV health in HIV-positive participants may in part be attributed to more frequent health care contact and provision of chronic disease care. Highlights: Good cardiovascular health (CVH) was observed in 53% of the study population. In global comparison, rural African study participants showed a good CVH score. HIV positivity was associated with a good CVH score. CVH score showed good agreement with carotid intima-media thickness.